PERBUATAN MELAWAN HUKUM DALAM PERTANGGUNGJAWABAN DOKTER TERHADAP TINDAKAN MALPRAKTIK MEDIS - Hadi, I Gusti Ayu Apsari (Jurnal Yuridis, 2018)
Medical malpractice remains a problem in health that has not been clearly regulated in a national legislation. But the elements are already contained in Act No. 36 of 2009 on Health which includes criminal law enforcement, administration and civil law. In the perspective of civil law a medical malpractice is an unlawful act conduct that complies with the provisions of The Civil Code. This research based on normative juridical method within primary dan secondary legal materials. The results of this study indicate that the lawsuit of unlawful act (onrechtamtige daad) in medical malpractice is regulated in Article 1365 of the Civil Code with elements :  1) the patient must experience a tort; 2) there are errors or missions (in addition to individuals, hospitals may have duty for errors or missions); 3) there are causal between tort and error; 4) The act is unlawful. In addition, the responsibility of the unlawful act against the medical malpractice ased on Article 1365 of the Civil Code is can be material and immaterial compensation that have a related between errors and torts.